Branding Design and Trademark Registration for Micro, Small dan Medium Enterprises (MSMEs) - Ida Nuraini; Happy Febrina Hariyani (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
The introduction of a product through a brand or brand that is easily remembered and recognized by consumers will have an impact on the development of the business. "Atiqa Handycraft" is one of the Micro, Small and Medium Enterprises that are members of the Family Welfare Improvement Business Group in Lowokwaru District, Malang City which produces bags, wallets, masks, book covers and mukena. Atiqa Handycraft's products are of good quality but have not been able to enter stores because there is no brand yet. In this mentoring activity, Partners are given an explanation of the importance of a Mark and are assisted on how to register a trademark. The results of the activity are the design of the Atiqa's brand and assistance for trademark registration to the Office of Micro, Small and Medium Enterprises of Malang City.